Угол обитания: Письма из Ostland’a в Ostland: 1941—1944 гг. [A Slice of Life: Letters to and from Ostland (1941—1944)] - Ravdin, Boris; Musachio, Benjamin (Slavica Revalensia, 2026)
We present a selection of annotated letters from 1941 and 1944 addressed to Gennadii Ivanovich Tupitsyn (1895, Rostov-on-Don – 1966, Riga), a Riga-residing educator with diverse interests in languages, literature, and geography. This valuable, multilingual collection comprising more than fifty letters illustrates “everyday life” (“povsednevnyi byt”) in Latvia during the period of German occupation. Tupitsyn’s family, colleagues, and former students wrote to the ailing instructor about a variety of seemingly prosaic topics: ration cards, pensions, job opportunities, dental procedures, harvests, book sales, etc. The specter of war nevertheless hovers in the background (and on occasion intrudes into the foreground) of this correspondence. In annotating these letters, we rely on primary sources, particularly daily newspapers (for example Tēvija, Slovo). This emphasis on contextualizing newspapers and periodicals recreates the atmosphere of the time, primarily as seen through the eyes of the Tupitsyn extended family as well as Tupitsyn’s colleagues. We also comment on these letters’ poetics, attending to the tropes, typos, and word signals embedded in the Russian, Latvian and German originals.